Initial validation of a new device for facial skin analysis. (17th November 2022) - Cook, Madison K.; Kaszycki, Margaret A.; Richardson, Irma; Taylor, Sarah L.; Feldman, Steven R.
Abstract: The field of dermatology is met with many subjective analysis methods. Due to the relative nature of subjective analysis methods, objective analysis methods with greater accuracy and reliability were developed. Many of these devices are either inaccessible to patients without being a part of a clinical trial, bulky, or costly. However, with the advances in artificial intelligence and handheld devices, measurement methods have become simplified. The purpose of our study was to validate an objective skin analysis software available on a handheld device by comparing it to a board-certified dermatologist's assessment. Participants of various ages and skin types were analyzed with the facial analysis system on an iPad Pro. The same photographs were ranked by a physician based on 14 common skin characteristics. The facial analysis system and the physician's rankings had a good agreement rate of 69%. The greatest agreement rates were with the assessment of erythema (83.7%) and wrinkles (81.6%) and the lowest with oiliness (53.1%). The analysis system's high re-test reliability and good agreement rates with physician assessment support its potential use in the clinical setting.